Oxidation Behaviour at 1100°C of HfC-Containing Co-Based Alloys (Journal of Material Science and Technology Research, 2017)
Cobalt alloys may be efficiently strengthened by hafnium carbides for uses at high temperature. However the presence of Hf in quantities high enough to allow significant creep-resistance may lead to particular behaviour in oxidation at high temperature. In this work three HfC-containing cobalt-based alloys were exposed to synthetic air at 1100‚°C for 50 hours, to observe their surface reactivity. The change in mass by oxidation, the general surface state, the oxide scales and subsurface changes specified by cross-sectional characterization were studied. They were compared to similar results obtained for hafnium-free cobalt alloys with the same chromium and carbon contents, considered as references. The presence of several weight % of hafnium obviously induced a real deterioration of the resistance against oxidation at 1100‚°C. This shows that these cobalt alloys must be improved for better resisting high temperature oxidation. This is compulsory to allow lifetime really benefiting from the mechanical strengthening brought by the HfC interdendritic network.